Reflections on reflection: an audit of students' use of structured models within specific assessments - NEILL, FREDA; TIMMINS, FIONA (My University, 2013)
This paper presents the results of an audit aimed to ascertain the extent to which using a structured model of reflection improved the quality of students? reflective assignments. An eight item anonymous audit tool was used to collect data from 221 student assessments. Findings reveal that student performance is directly related to use of structured model of reflection. The majority of students who did not utilise a structured model, to support their reflections (89% n=85), scored less than 65%, most of these scored less than 60% (68% n=68). Moreover most students who did not achieve a pass mark, did not use a model as a guide (69% n=11). Nursing students? performance at the assessment was enhanced by structured model use. Their inclusion of a reflective component within their essay appeared to improve not only their reflective skills, but enhanced higher levels of learning. While many students performed very well without a structured approach, overall students ought to be encouraged to incorporate a clear structure of reflection and engage in all phases of the cycle.
Procedia - Social and Behavioral Sciences
NET 2012 23rd International Networking for Healthcare Education
PUBLISHED
￼
Robinson College Cambridge, UK
Keywords: Reflection; nursing student; Identities in Transformation